DC fault detection and clearance in VSC-HVDC systems - Yeap, Yew Ming (2018)
Today’s electric grid is mostly based on alternating current (AC), as well as the loads. The advancement of voltage source converter (VSC) has paved way for the emergence of VSC-HVDC transmission systems opening up the possibility to build multi-terminal DC (MTDC) grid in future. Before we reach that mark, there are a lot of open points to be answered. One of the critical topics for such DC grid is the protection.